Lighting Level Measuring Device Based On Web Using Kalman Filter Method - Dika Rahayu Widiana; Tabah Uji Antoro; Khoirul Hasin (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2022)
The need for lighting in each room depends on the activities carried out. According to the Indonesian National Standards (SNI) 03-6575-2001, the minimum recommended lighting strength for lecture hails is 200 lux to 250 lux and for laboratories is 300 lux to 500 lux. In measuring the level of lighting in a room, a tool called a lux meter is needed. But as is known light sensor is a sensor that quite sensitive. In this research the writer uses the Kalman Filter method to increase the accuracy and precision of the BH1750 lighting level sensor. In addition, this tool is also integrated with a website to make it easier for users to monitor measurement results both stored and in real-time. Tool testing is done by measuring 28 different locations. The test scheme is adjusted to the standard operating procedure for measuring light intensity which refers to SNI 16-7062-2019. From the test results for measurements using the Kalman Filter method, the stability level is 78.57%, the precision level is 1.46% and the accuracy error value is 0.92%. While the test results for measurements without the Kalman Filter method obtained a stability level of 53.57%, a precision level of 2.80% and an accuracy error value of 2.77%.